COGNITIVE BIAS MODIFICATION THERAPY UNTUK MENGATASI KECANDUAN GAME ONLINE - Linda Fitria; Yeni Karneli (Jurnal Al-Fatih, 2019)
Online games are activities that are liked by various groups, ranging from children, adolescents, and even adults. Behavior playing online games in adolescents tends to have a negative impact, one of which reduces the effective time of learning. In addition, this condition can potentially cause addiction to online games. As for indications of online gaming addiction is a lack of self-control, unable to determine the priority scale, have psychological disorders both related to personal, social, educational, and community. These indications can last for 12 months. If this is not handled properly, it can be detrimental to teenagers who are addicted to online games. So we need treatment to overcome this online game addiction, one of them with cognitive bias modification therapy. This article will describe the handling related.